THU0522 Methotrexate: A Novel Mechanism for Vasculoprotection in Chronic Systemic Inflammation. (10th June 2014) - Thornton, C.; Alrashed, F.; Calay, D.; Birdsey, G.; Haskard, D.; Boyle, J.; Mason, J.
Abstract : Background: Chronic systemic inflammation is associated with endothelial dysfunction leading to accelerated atherosclerosis. Although treatment of inflammatory disease has significantly improved, there is as yet no specific strategy to protect the vasculature and retard the onset of cardiovascular disease (CVD).Clinical data suggests that long term low-dose methotrexate (MTX) reduces CV mortality in rheumatoid arthritis. However, little is known about the mechanisms underlying this. Known actions of MTX include inhibition of purine synthesis enzymes, resulting in intracellular accumulation of adenosine monophosphate (AMP) and 5-aminoimidazole-4-carboxamide ribonucleotide. These are activators of AMP-activated protein kinase (AMPK), a ubiquitous signalling kinase that regulates cytoprotective genes in endothelial cells (EC) including manganese superoxide dismutase (MnSOD) and heme oxygenase-1 (HO1). We hypothesised that MTX exerts beneficial protective effects on vascular endothelium via activation of AMPK which enhance its ability to withstand inflammatory-mediated injury. Objectives: This study aimed to establish whether MTX can activate AMPK and induce cytoprotective gene expression in EC, explore the intermediaries involved, study the functional relevance of this pathway and whether MTX affects endothelial cell survival.Finally, we planned to treat a model of inflammatory vascular disease with MTX to establish whether it protects vascular endothelium in vivo. Methods: In vitro studies of the effects of MTX were carried out on human umbilical vein EC (HUVEC), using western blotting, qRTPCR, flow cytometry and chromatin immunoprecipitation.Inhibition of signalling pathways was achieved using short interfering RNA. The vascular effects of MTX in vivo were studied in the murine (NZWxBXSB) F1 (WBF1) model of SLE vasculopathy.Animals were treated with MTX 1mg/kg weekly by intraperitoneal injection for 4 weeks.Aortic tissue was used in Western blots and in frozen sections for immunofluorescence.Myocardial sections were stained with periodic acid-Schiff and picrosirius red. Results: Treatment of HUVEC with MTX 100nM for 48h phosphorylated AMPKα and induced expression of several cytoprotective genes, notably MnSOD and HO1, while siRNA depletion of AMPK attenuated these changes.MTX treatment led to AMPK-dependent phosphorylation of the transcription factor CREB, siRNA depletion of CREB1 reduced MnSOD and HO1 induction by MTX, and chromatin immunoprecipitation demonstrated binding of CREB1 to the MnSOD promoter in MTX-treated samples.The magnitude of MnSOD induction was preserved when HUVEC were pre-treated with TNFα to mimic a dysfunctional endothelium.Finally, MTX protected HUVEC against apoptosis induced by glucose deprivation. Treating WBF1 mice with MTX reduced end-organ damage and the severity of the vasculopathy.Increased aortic expression of MnSOD and phosphorylated AMPK and reduced ICAM1 expression was observed, confirming that low dose weekly MTX can activate AMPK in the vasculature in vivo, and is associated with improvement in vascular inflammation. Conclusions: MTX activates an AMPK-CREB pathway in endothelium leading to enhanced expression of cytoprotective genes and protection against apoptosis in vitro and inflammatory vascular injury in vivo. This novel mechanism may explain its observed benefits in reducing CVD in chronic systemic inflammation. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4685